The Indonesia-Malaysia cultural heritage disputes: A case study of the Pendet dance and rasa Sayange folk song - Lai, Yew Meng; Yusten Karulus (Penerbit UMS, 2019)
This article analyses the role of nationalism and power politics (external/domestic) in shaping Indonesia’s relations with Malaysia during the administration of President Susilo Bambang Yudhoyono (SBY). More specifically, it examines how nationalism, namely domestic nationalist pressure interacts with other external-domestic determinants in shaping Indonesia’s external behaviour and options towards Malaysia when managing the cultural heritage disputes, with particular attention given to Malaysia’s alleged claims of proprietorship over the Pendet dance and Rasa Sayange folk song. By adopting a neoclassical realist construct, this study seeks to address the pertinent questions of why, how, when and to what extent nationalism affects the perceptions and calculation of the SBY administration and Jakarta’s policy options during their altercations over the two cultural heritage debacles. Special attention is given to examining the interactions between domestic nationalist pressure and the related external-domestic determinants influencing Indonesia’s foreign policy towards Malaysia, to assess the extent to which nationalism constrained the SBY administration’s handling of the related episodes of the cultural heritage disputes. This study found the salience of nationalism and/or domestic nationalist pressure in constraining/affecting SBY administration’s management of the cultural heritage disputes affecting the Indonesia-Malaysia bilateral ties to be dependent on the Indonesian state-elites’ perceptions/calculation of the external-domestic conditions, namely their domestic political resolve vis-à-vis nationalist forces and Indonesia’s relative power position compared with Malaysia, which predisposed specific foreign policy-options during the given time period and context.